PERFORMANCE OF PROMISING ECORACES OF ERI (PHILOSAMIA RICINI) IN AGROCLIMATIC CONDITIONS OF WESTERN ODISHA - RAY, PRITI PRAGYAN; T. V. RAO; DASH, PURUSHATTAM (The Bioscan, 2010)
Culturing non-mulberry silkworm Eri (Philosamia ricini) is a traditional vocation in Eastern and North Eastern part of India. At present the variety of Eri silkworm cultured by farmers of Odisha has very low silk yield potential. The Eri eggs supplied to the farmers of Odisha are from a mixed population of several varieties. However in Assam and Meghalaya of North East India exist several ecoraces of Philosamia ricini in isolated pockets, separated by cultural and geographical barriers.The objective of the the project is to examine the ecoraces of North east India namely Borduar, Titabar and Mendipathar in order to augment Eri silk production in Odisha. Assessment of these ecoraces was done under the local agro-climatic conditions taking morphodevelopmental parameters. For this larval and cocoon characteristics, fecundity, mortality and silk production were investigated. Further the performance of rearing, cocoon and grainage performance were studied. The one way ANOVA analysis reveals that the SR% of the three ecoraces is significantly higher than present mixed variety of unknown genetic origin (p d”0.05). The data suggests that these ecoraces can be used for higher silk yield by the Eri farmers of Odisha.